Thallium isotope evidence for a permanent increase in marine organic carbon export in the early Eocene - Nielsen, S; Mar-Gerrison, S; Gannoun, A; LaRowe, D; Klemm, V; Halliday, A; Burton, K; Hein, JR (2009)
The first high resolution thallium (Tl) isotope records in two ferromanganese crusts (Fe-Mn crusts), CD29 and D11 from the Pacific Ocean are presented. The crusts record pronounced but systematic changes in 205Tl/ 203Tl that are unlikely to reflect diagenetic overprinting or changes in isotope fractionation between seawater and Fe-Mn crusts. It appears more likely that the Fe-Mn crusts track the Tl isotope composition of seawater over time. The present-day oceanic residence time of Tl is estimated to be about 20,000 yr, such that the isotopic composition should reflect ocean-wide events. New and published Os isotope data are used to construct age models for these crusts that are consistent with each other and significantly different from previous age models. Application of these age models reveals that the Tl isotope composition of seawater changed systematically between ~ 55 Ma and ~ 45 Ma. Using a simple box model it is shown that the present day Tl isotope composition of seawater depends almost exclusively on the ratio between the two principal output fluxes of marine Tl. These fluxes are the rate of removal of Tl from seawater via scavenging by authigenic Fe-Mn oxyhydroxide precipitation and the uptake rate of Tl during low temperature alteration of oceanic crust. It is highly unlikely that the latter has changed greatly. Therefore, assuming that the marine Tl budget has also not changed significantly during the Cenozoic, the low 205Tl/ 203Tl during the Paleocene is best explained by a more than four-fold higher sequestration of Tl by Fe-Mn oxyhydroxides compared with at the present day. The calculated Cenozoic Tl isotopic seawater curve displays a striking similarity to that of S, providing evidence that both systems may have responded to the same change in the marine environment. A plausible explanation is a marked and permanent increase in organic carbon export from ~ 55 Ma to ~ 45 Ma, which led to higher pyrite burial rates and a significantly reduced flux of Fe-Mn oxide removal as a result of increased biological uptake of Fe and Mn. © 2008 Elsevier B.V. All rights reserved.